Oscillation Criteria for Second-Order Nonlinear Dynamic Equations on Time Scales - Shao-Yan Zhang; Qi-Ru Wang (Abstract and Applied Analysis)
This paper is concerned with oscillation of second-order nonlinear dynamic equations of the form on time scales. By using a generalized Riccati technique and integral averaging techniques, we establish new oscillation criteria which handle some cases not covered by known criteria.